Doctors' decisions when disclosing their mental ill-health. (4th May 2019) - Rees, S; Cohen, D; Marfell, N; Robling, M
Abstract: Background: Understanding of what prevents doctors from seeking help for mental ill-health has improved. However, less is known about what promotes timely disclosure and the nature of doctors' decision making. Aims: This study aimed to define how doctors make decisions about their own mental ill-health, and what facilitates disclosure. It explored the disclosure experiences of doctors and medical students; their attitudes to their decisions, and how they evaluate potential outcomes. Methods: Qualitative, semi-structured interviews with UK doctors and medical students with personal experience of mental ill-health. Participants were recruited through relevant organizations, utilizing regular communications such as newsletters, e-mails and social media. Data were subject to a thematic analysis. Results: Forty-six interviews were conducted. All participants had disclosed their mental ill-health to someone; not all to their workplace. Decision making was complex, with many participants facing multiple decisions throughout their careers. Disclosures were made despite the many obstacles identified in the literature; participants described enablers to and benefits of disclosing. The importance of appropriate responses to first disclosures was highlighted. Conclusions: Motivations to disclose mental ill-health are complex and multifactorial. An obstacle for one was an enabler for another. Understanding this and the importance of the first disclosure has important implications for how best to support doctors and medical students in need.